2012
DOI: 10.1016/j.exger.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Levels of cerebrospinal fluid neurofilament light protein in healthy elderly vary as a function of TOMM40 variants

Abstract: Neurofilament light (NFL) proteins in cerebrospinal fluid (CSF) are a marker of neuronal damage, especially subcortical axonal injury and white matter disease. Subjects with Alzheimer’s disease (AD) have shown elevated levels of CSF NFL as compared to controls. However, the presence of the APOE ε4 allele, an established risk factor for AD, was not found to associate with higher CSF NFL concentrations. We examined whether TOMM40 variants, which have been reported to influence age of onset of AD and are in linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The 523 VL poly T resulted in significantly higher expression than the S poly T. These results suggest that the 523 locus may contribute to LOAD susceptibility by modulating the expression of TOMM40 and/or APOE transcription [55]. Recent studies also suggest that the TOMM40 gene rs10524523 ("523") variable length poly T repeat polymorphism is associated to a certain extent with similar AD phenotypes as those reported for APOE, such as brain white matter changes [56,57] or different biomarkers [58][59][60][61]. In addition, the TOMM40 rs2075650 G allele may be a risk factor for the development of depression [62] and sporadic inclusion body myositis [63].…”
Section: Introductionmentioning
confidence: 57%
“…The 523 VL poly T resulted in significantly higher expression than the S poly T. These results suggest that the 523 locus may contribute to LOAD susceptibility by modulating the expression of TOMM40 and/or APOE transcription [55]. Recent studies also suggest that the TOMM40 gene rs10524523 ("523") variable length poly T repeat polymorphism is associated to a certain extent with similar AD phenotypes as those reported for APOE, such as brain white matter changes [56,57] or different biomarkers [58][59][60][61]. In addition, the TOMM40 rs2075650 G allele may be a risk factor for the development of depression [62] and sporadic inclusion body myositis [63].…”
Section: Introductionmentioning
confidence: 57%
“…Furthermore, Bruno et al showed an increase in CSF cortisol concentration, which suggests hippocampal damage, in individuals who carry two copies of the longer 523 alleles[18]. In another study, they also showed that the CSF levels of neurofilament light proteins, markers of neuronal damage that are elevated in LOAD patients, were significantly higher in subjects with two copies of the longer 523 alleles[19]. Recently, Crenshaw and colleagues thoroughly discussed the observation of variable effects of the 523 VL allele [11].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the first group were recruited via advertisements in local newspapers and flyers, or from the Memory Education and Research Initiative (MERI) program at the Nathan Kline Institute for Psychiatric Research; participants' recruitment was part of a study on late-life MDD (Bruno et al, 2012; Bruno, Nierenberg, Ritchie, Lutz & Pomara, 2012; Pillai et al, 2012; Pomara et al, 2012). All participants provided formal consent prior to testing and received compensation for up to $450.00 for their time and efforts.…”
Section: Methodsmentioning
confidence: 99%